PREGNANCY AND DELIVERY IN A PATIENT WITH AN ECTOPIC KIDNEY TRANSPLANT AND BILLATERAL HEARING LOSS - Macura, Maja; Dugalic, Stefan; Todorovic, Jovana; Božić, Dragana; Gojnic, Miroslava (Medical Research, 2023)
Introduction Pregnancy management and delivery mode in kidney transplant patients are still the subject of debate. The goal is to achieve the balance between mother’s underlying disease treatment and optimal conditions for fetal development and maturation. Case study This is a 36-year-old patient whose first pregnancy was complicated by kidney transplantation 11 years ago. During hospitalization, the values of all renal function parameters and cyclosporine concentration in the blood were regularly monitored, and nephrology and urology consultations were regularly performed. Bearing in mind the pelvic presentation of the fetus, ectopic localization of the transplanted kidney and comorbidities such as deafness, gestational diabetes and gestational hypertension, the delivery was completed by caesarean section with the presence of a urologist and a healthy male child was born. Conclusion With current monitoring of the literature, team work, intensive supervision and adequate therapy for the mother and the fetus, it is possible to manage the pregnancy in complicated transplant patients and achieve outcomes equal to physiological pregnancy.